2004
DOI: 10.1038/sj.eye.6701497
|View full text |Cite
|
Sign up to set email alerts
|

Blinking and superficial punctate keratopathy in patients with diabetes mellitus

Abstract: Aim To evaluate blinking patterns in patients with diabetes mellitus and whether blinking contributes to the formation of superficial punctate keratopathy in diabetic patients. Methods We examined 163 patients with type II diabetes mellitus and 76 without diabetes. Blinks were recorded, analysed using six parameters, and compared between patients with and without diabetes. Multivariate regression analysis was performed to assess the influence of other ocular factors, such as status of tear lipid layer, tear br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 11 publications
3
29
0
Order By: Relevance
“…Disease or any damage to these neurons leads to dry eye in an animal model [35]. Two human studies have previously reported a compromised tear lipid layer in DM patients, as confirmed in the current study [8, 36]. Clinical observation of noncontiguous or absent lipid layers is associated with significantly increased tear film evaporation [37], one of the key factors in dry eye development [38].…”
Section: Resultssupporting
confidence: 76%
“…Disease or any damage to these neurons leads to dry eye in an animal model [35]. Two human studies have previously reported a compromised tear lipid layer in DM patients, as confirmed in the current study [8, 36]. Clinical observation of noncontiguous or absent lipid layers is associated with significantly increased tear film evaporation [37], one of the key factors in dry eye development [38].…”
Section: Resultssupporting
confidence: 76%
“…28 The average blink rate is also lower in patients with diabetes than in control subjects. 29 Accordingly, pinguecula probably develops secondary to inflammation caused by friction between the bulbar and palpebral conjunctivae due to dryness. The levels of inflammatory cytokines in tear fluid are increased by delayed clearance of tears, 30 so obliteration of the tear meniscus and delayed tear clearance could also aggravate superficial ocular inflammation, 31,32 leading to pinguecula.…”
Section: Discussionmentioning
confidence: 99%
“…[22] In diabetic patients, corneal thickness is increased while there is a thinning of the epithelium [18], which is consistent with findings of lower basal epithelial cell density in T2D patients. [23] This is confirmed by observations that hyperglycemia also directly and significantly alters their structure and function of corneal epithelial cells, resulting in basal cell degeneration [14, 22, 24], decreased [25, 26] or increased [27] cell proliferation, superficial punctate keratitis [28], breakdown of barrier function [29, 30], fragility [31], and abnormal deposition of laminin and type IV collagen. [32] Given the significant impact on diabetes on the corneal epithelium, diabetic keratopathy is also termed diabetic corneal epitheliopathy.…”
mentioning
confidence: 77%
“…[46] The sensory nerves are responsible for sensations of dryness, temperature, touch, and pain, and play important roles in the blink reflex, wound healing, and tear production. [28, 4752] Corneal nerves are largely derived from the ophthalmic division of the trigeminal nerve. Dozens of major stromal nerve bundles enter the cornea from the limbus and penetrate into the mid-stroma.…”
mentioning
confidence: 99%